2022
DOI: 10.3390/genes13060987
|View full text |Cite
|
Sign up to set email alerts
|

Fish as Model Systems to Study Epigenetic Drivers in Human Self-Domestication and Neurodevelopmental Cognitive Disorders

Abstract: Modern humans exhibit phenotypic traits and molecular events shared with other domesticates that are thought to be by-products of selection for reduced aggression. This is the human self-domestication hypothesis. As one of the first types of responses to a novel environment, epigenetic changes may have also facilitated early self-domestication in humans. Here, we argue that fish species, which have been recently domesticated, can provide model systems to study epigenetic drivers in human self-domestication. To… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 100 publications
(158 reference statements)
0
1
0
Order By: Relevance
“…Features of self-domestication have been found altered in people with ASD (Benitez-Burraco, et al 2016) and SCZ (Benitez-Burraco, et al 2017). Furthermore, loci implicated in mammal domestication appear to be dysregulated in the blood of individuals with ASD (Benitez-Burraco 2020), whereas genes exhibiting methylation changes in ASD and SZ are enriched in processes such as neural crest differentiation and ectoderm differentiation (Anastasiadi, et al 2022). Likewise, a previous study showed the polygenic component of psychiatric disorders and behavioral traits is associated with the phonological complexity of European languages in relation to local adaption (Polimanti, et al 2018), with types of languages being impacted, as noted, by changes in self-domestication levels (Benitez-Burraco and Progovac 2020).…”
mentioning
confidence: 99%
“…Features of self-domestication have been found altered in people with ASD (Benitez-Burraco, et al 2016) and SCZ (Benitez-Burraco, et al 2017). Furthermore, loci implicated in mammal domestication appear to be dysregulated in the blood of individuals with ASD (Benitez-Burraco 2020), whereas genes exhibiting methylation changes in ASD and SZ are enriched in processes such as neural crest differentiation and ectoderm differentiation (Anastasiadi, et al 2022). Likewise, a previous study showed the polygenic component of psychiatric disorders and behavioral traits is associated with the phonological complexity of European languages in relation to local adaption (Polimanti, et al 2018), with types of languages being impacted, as noted, by changes in self-domestication levels (Benitez-Burraco and Progovac 2020).…”
mentioning
confidence: 99%